Ascitic fluid polymorphic nuclear cell count impacts on outcome of cirrhotic patients with ascites. Issue 5 (June 2019) - Simbrunner, Benedikt; Röthenbacher, Annika; Haslacher, Helmuth; Bauer, David; Chromy, David; Bucsics, Theresa; Schwabl, Philipp; Paternostro, Rafael; Scheiner, Bernhard; Trauner, Michael; Mandorfer, Mattias; Schwarzinger, Ilse; et al.
Background: Spontaneous bacterial peritonitis (SBP) is defined as an ascitic polymorphonuclear cell count (A-PMN) > 250 cells/µl. Objective: We aimed to investigate the prognostic value of ascitic fluid cell counts in patients without SBP. Patients and methods: A total of 178 patients were included and stratified by ascitic cell counts at index paracentesis: A-LEUK-low (<250/µl), A-LEUK-intermediate (250–500/µl) and A-LEUK-SBP (>500/µl) for leukocytes; A-PMN-low (<125/µl), A-PMN-intermediate (125–250/µl) and A-PMN-SBP (>250/µl) for PMN cells. Results: One-year mortality was comparable between group A-LEUK-SBP (53.9%) and patients with subclinical cell counts (34.5% for A-LEUK-low, 43.5% for A-LEUK-intermediate, log-rank p  = 0.547). However, we observed an increase in one-year mortality already in group A-PMN-intermediate with 75% and A-PMN-SBP with 80.9% (vs 40.5% for A-PMN-low, log-rank p  = 0.016). Importantly, increases of A-PMN cell counts between two paracenteses were associated with increased mortality: per 100 cells/µl increase of absolute A-PMN cell count: hazard ratio (HR): 1.03 (95% confidence interval (CI): 1.01–1.06), p  = 0.005; per 5% increase of relative PMN cell count: HR: 1.15 (95% CI: 1.06–1.26), p  = 0.001. Conclusion: Patients with PMN cell counts of 125–250/µl are at high risk for mortality, which was very similar to SBP patients with PMN cell counts >250/µl. This highlights the need for preventive strategies. The prognostic value of changes in relative ascitic PMN cell counts should be evaluated in future studies.